Toward AI-Enchanted English Teaching in Higher Education: Preferences, Potential Opportunities, and Challenges of the Implementation - Tatipang, Devilito Prasetyo; Dollah, Syarifuddin; Mahmud, Murni; Asrifan, Andi; Liando, Nihta V. F.; Pontillas, Marlon S (STAIN Majene, 2026)
This study explores the preferences, potential opportunities, and challenges associated with the implementation of AI in English language instruction in higher education. Mix method was adopted in this study, by using a questionnaire and semi-structure interview to collect data. 15 English lecturers with approximately 5-10 years of teaching experiences involved in the sample, and 5 of them were interviewed. The result shows that preferences in AI-Implemented English teaching within higher education are multifaceted. Lecturers often prefer AI systems that seamlessly augment their teaching methodologies rather than replace them. Additionally, preferences also extend to the number of AI tools, such as ChatGPT, ELSA Speak, smalltool.ai, paraphrase.io, and language generation systems, etc., being prominent choices. Furthermore, AI transforms English language teaching by personalizing student learning, providing modern teaching and learning tools, delivering timely and objective performance feedback, accelerating core literacy skills, creating immersive virtual reality simulations, and enhancing language acquisition. However, these potential opportunities must be balanced against challenges like cost, data security, and the potential dehumanization of education. As AI continues to evolve, a thoughtful and adaptable approach to its implementation is paramount to harness its full potential while preserving the integrity of higher education.